2016
DOI: 10.1007/s12262-016-1500-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Factors Affecting the Sentinel Lymph Node Metastasis in Patients with Breast Cancer

Abstract: Sentinel lymph node biopsy has become the routine procedure in axilla-negative breast cancer patients at most medical centers for axillary staging and local control in the recent years. Sentinel lymph node is the only focus in axillary lymph metastasis in a large portion of patients. In our trial, we investigated the clinical and pathological factors that affect the positive status of sentinel lymph node. We included 89 patients, who underwent sentinel lymph node biopsy (SLNB) with methylene blue and/or techne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…A previous study has found a correlation between ALN metastasis and LVI in BC. 33 In this study, MRI-ALN status, as a noninvasive MRI characteristic, showed important discriminative performance for LVI assessment. In addition, previous studies indicated that BES was associated with the prognosis after neoadjuvant chemotherapy and ALN metastasis burden in IBC.…”
Section: Discussionmentioning
confidence: 70%
“…A previous study has found a correlation between ALN metastasis and LVI in BC. 33 In this study, MRI-ALN status, as a noninvasive MRI characteristic, showed important discriminative performance for LVI assessment. In addition, previous studies indicated that BES was associated with the prognosis after neoadjuvant chemotherapy and ALN metastasis burden in IBC.…”
Section: Discussionmentioning
confidence: 70%
“…Digital mammography is one of the important imaging tools for breast cancer screening and diagnosis. There have been many reports on prediction of axillary lymph node metastasis [3][4][5] and on digital mammography screening [6][7][8][9]. However, there has been no report on predicting LVI of breast cancer based on imaging patterns of digital mammography, except a little literature in which MRI findings were used for prediction [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Digital mammography is one of the important imaging tools for breast cancer screening and diagnosis. There have been many reports on prediction of axillary lymph node metastasis [3][4][5] and on digital mammography screening [6][7][8][9]. However, there has been no report on predicting LVI of breast cancer based on imaging patterns of digital mammography, except a little literature in which MRI findings were used for prediction [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%